2011
DOI: 10.1063/1.3594200
|View full text |Cite
|
Sign up to set email alerts
|

Granular collapse in a fluid: Role of the initial volume fraction

Abstract: The collapse of a granular column in a viscous liquid is experimentally investigated. The morphology of the deposits is shown to be mainly controlled by the initial volume fraction of the granular mass and not by the aspect ratio of the column, an observation which differs from dry granular collapse. Two different regimes are identified corresponding to initially loose and dense packings. Loose packings give rise to thin and long deposits, the dynamics being fast. A positive liquid pressure is measured below t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

31
265
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 171 publications
(314 citation statements)
references
References 31 publications
31
265
1
Order By: Relevance
“…In particular, since the grains initially filling the hoppers are arranged in dense packing, the flow at the aperture, necessary involving shearing, may induce locally dilation and the sucking of water in the hopper, as it is the case in quick sands for instance. In [5], the pressure at the bottom of dense granular columns immersed in water at the onset of collapsing was found to be negative. Of course the systems are different, but the same mechanism may apply.…”
Section: Tall and Short Columns For Immersed Hoppersmentioning
confidence: 99%
“…In particular, since the grains initially filling the hoppers are arranged in dense packing, the flow at the aperture, necessary involving shearing, may induce locally dilation and the sucking of water in the hopper, as it is the case in quick sands for instance. In [5], the pressure at the bottom of dense granular columns immersed in water at the onset of collapsing was found to be negative. Of course the systems are different, but the same mechanism may apply.…”
Section: Tall and Short Columns For Immersed Hoppersmentioning
confidence: 99%
“…The column is anchored via capillary forces with the hydrophobic substrate at the bottom and is slightly flared close to the anchoring region. Under an identical protocol, hydrophilic beach sand instead slumps to form a canonical sandpile [31].…”
Section: Construction Of a Submerged Free-standing Columnmentioning
confidence: 99%
“…In the present study, we consider a saturated mixture, in which case the interstitial fluid may affect the value of the neutral angle. Rondon et al (2011) investigated granular collapses in a fluid and found there to be a roughly linear proportion between the initial solid volume fraction and the final deposition slope. In Coulomb-mixture theory, the solid normal stress at the base is assumed to be a fraction, 1 − f , of the total basal normal stress.…”
Section: Erosion-deposition Ratementioning
confidence: 99%